Towards a Conceptual Model of Users’ Expectations of an Autonomous In-Vehicle Multimodal Experience - Ecem Berfin Ince; Kyungjoo Cha; Junghyun Cho (Human Behavior and Emerging Technologies)
People are expected to have more opportunities to spend their free time inside the vehicle with advanced vehicle automation in the near future. This will enable people to turn their attention to desirable activities other than driving and to have varied in-vehicle interactions through multimodal ways of conveying and receiving information. Previous studies on in-vehicle multimodal interactions primarily have focused on making users evaluate the impacts of particular multimodal integrations on them, which do not fully provide an overall understanding of user expectations of the multimodal experience in autonomous vehicles. The research was thus designed to fill the research gap by posing the key question “What are the critical aspects that differentiate and characterise in-vehicle multimodal experiences?” To answer this question, five sessions of design fiction workshops were separately conducted with 17 people to understand the users’ expectations of the multimodal experience in autonomous vehicles. Twenty-two subthemes of users’ expected tasks of multimodal experience were extracted through thematic analysis. The research found that two dimensions, attention and duration, are critical aspects that impact in-vehicle multimodal interactions. With this knowledge, a conceptual model of the users’ in-vehicle multimodal experience was proposed with a two-dimensional spectrum, which populates four different layers: sustained, distinct, concurrent, and coherent. The proposed conceptual model could help designers understand and approach users’ expectations more clearly, allowing them to make more informed decisions from the initial stages of the design process.